KEBUTUHAN PENDIDIKAN KETERAMPILAN BAGI PENCARI KERJA DI KECAMATAN MAJE KABUPATEN KAUR PROVINSI BENGKULU - Muchtar, Sazili (Universitas Muhammadiyah Magelang, 2009)
This study aims to identify the types of skills required job seekers in the district of Bengkulu Province Maje Kaur Disctrict.